TImproving Students’ Pronunciation Using Auto Speech Recognition Software to the Tenth Grade Language Major Students at SMAN 1 Lawang - Muhammad Subkhan (Language-Edu, 2020)
Clear pronunciation is important in order to communicate well in English. Unfortunately, the ten grader students of language major at SMAN 1 Lawang find difficulties to pronounce English words in classroom activity. This research is classroom action research because the aim is to figure out a solution to solve the pronunciation problem experienced by ten grader students of language major at SMAN 1 Lawang with the help of proper teaching media. The technology of auto speech recognition is the most suitable program for pronunciation improvements. This research is using one of the auto speech recognition which namely “Speech Text & Text Speech in All Languages” developed by SoftWiz. This research applied audio feedback activity with several adjustments. The adjustments were the use of auto speech recognition program that operated using android mobile phone and the use of google voice to replace the tape recorder voice. This research involved 31 ten grade students of language major. The result was a consistent improvement of students’ pronunciation in every session which was proven by the consistent class’s average score improvement, therefore, it proves that the strategy was arguably successful to be a solution of the students’ pronunciation problem.Keywords: Pronunciation, Audio Feedback, Auto Speech Recognition